Improving the Competence of Cadet Caregivers Using the Pancasila Character Development - Febiyanti, Herlina; Yuniar, Dwi Candra; Putra, Iwansyah; Setiawan, Ariyono (Graduate Program Magister Manajemen Pendidikan, 2022)
This study aimed at determining the relationship between the development of the character of cadets and the improvement of the competence of caregivers of the Palembang Aviation Polytechnic so that it can be known what competencies are needed by caregivers so that they can develop the character of cadets. Â This research was conducted at the Palembang Aviation Polytechnic in April 2022 to October 2022. The method used in this study is descriptive. Descriptive is an assessment that does not use mathematical, statistical or computer models. The data collection technique uses questions in the form of questionnaires through google forms, observations made by the author, as well as interviews with cadets and caregivers of the Palembang Aviation Polytechnic. The study population was all cadets and caregivers of the Palembang Aviation Polytechnic by taking sample data as a result of responses from respondents. The data processing will use Pearson's Product Moment method to determine the correlation between character development variables and caregiver competency improvement variables. The success of a program in the implementation of Pancasila Character development requires support from various parties in its implementation.